Investigating Students’ Mathematical Problem-Solving Abilities in the Context of Social Arithmetic through the Lens of Learning Styles - Andriani, Susi; Ermika, Tia; Izzati, Nur; Putri, Alyana Rahmadani; Mardani, Hesti Setyo (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study investigates how students solve mathematical problems in social arithmetic and examines the influence of different learning styles on their problem-solving performance. Although mathematical problem solving has been widely studied, limited attention has been given to how students’ learning styles interact with specific domains such as social arithmetic, which requires both conceptual understanding and procedural fluency. The study involved 20 seventh-grade students from SMPN 013 Satu Atap Bukit Bestari, Indonesia, and employed a qualitative descriptive design. Three instruments were used: a learning style questionnaire to categorize students into visual, auditory, and kinesthetic groups; a written test structured according to Polya’s four stages of problem solving; and semi-structured interviews to explore students’ reasoning processes in each stage. The findings showed that kinesthetic learners achieved the highest results across all indicators of problem solving. Auditory learners were proficient in understanding problems and planning strategies but struggled with evaluating their answers, while visual learners displayed strong initial comprehension but faced challenges in developing and implementing solution plans. Classroom elements such as group discussions and oral presentations were found to enhance engagement, particularly for kinesthetic learners. Overall, the study highlights the importance of aligning instructional approaches with students’ learning styles to improve mathematics learning outcomes. These results provide empirical support for differentiated instruction in mathematics, especially for context-based topics like social arithmetic that remain underexplored in current learning styles research.